2021
DOI: 10.1097/cad.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and mortality risk among extensive-stage small-cell lung cancer patients in mainland China: impacts of hypertension, type 2 diabetes mellitus, and chronic hepatitis B virus infection

Abstract: The present study investigated the impact of major comorbidities, including hypertension, type 2 diabetes mellitus (T2DM), and chronic hepatitis B virus (HBV) infection, on the progression-free survival (PFS) and overall survival (OS) of extensive-stage small-cell lung cancer (ES-SCLC) patients in China. Patients having a pathologic diagnosis of ES-SCLC between 2009 and 2017 were enrolled and grouped according to their specific comorbidities. The PFS and OS for each group were evaluated using the Kaplan–Meier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“… 3 , 18 , 20 , 21 Patients with extensive‐stage SCLC were predominantly smokers (75%) and male (80.3%), and the most common initial symptoms were mainly cough (54%), dyspnea (10%), bone pain (10%), asymptomatic (12%), and paraneoplastic syndromes (11%). 22 The most common comorbidities were hypertension, diabetes mellitus, 23 and chronic obstructive pulmonary disease, 24 accounting for 33.7%, 19%, and 7% of cases, respectively. The most common extra‐thoracic metastatic organs were bone, liver, brain, and adrenal gland, at 36.3%, 24%, 7%, 16.3%, and 15.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 18 , 20 , 21 Patients with extensive‐stage SCLC were predominantly smokers (75%) and male (80.3%), and the most common initial symptoms were mainly cough (54%), dyspnea (10%), bone pain (10%), asymptomatic (12%), and paraneoplastic syndromes (11%). 22 The most common comorbidities were hypertension, diabetes mellitus, 23 and chronic obstructive pulmonary disease, 24 accounting for 33.7%, 19%, and 7% of cases, respectively. The most common extra‐thoracic metastatic organs were bone, liver, brain, and adrenal gland, at 36.3%, 24%, 7%, 16.3%, and 15.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated blood pressure has been previously shown to influence thrombosis via hypercoagulability, low blood flow, and endothelial damage, which increases the risk of vascular wall damage, promoting or aggravating the formation of thrombus ( 10 - 12 ). Hypertension has been reported as a risk factor of VTE in patients with idiopathic pulmonary fibrosis ( 13 ), and is associated with a significantly reduced overall survival (OS) for patients with lung cancer ( 14 ). However, to the best of our knowledge, this current study is the first to investigate the relationship between chronic hypertension and PE in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the mean progression-free survival of patients without diabetes was 9 months, while it was significantly reduced for patients with diabetes (5 months (P < 0.0001)). They also reported that the overall survival of patients with diabetes was significantly shorter than that of patients without diabetes (HR: 1.455; 95% CI: 1.134 - 1.868; P = 0.003) [ 50 ]. Kelkar and colleagues investigated the association between diabetes and prostate cancer-specific mortality.…”
Section: Discussionmentioning
confidence: 99%